Three Cheers for Lord Denman: Reformers, the Irish, and Jury Reforms in Nova Scotia, 1833-1845 - Blake Brown, R. (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2005)
AbstractThis article explores the important place of the jury in the relationship between law, politics, and state in pre-Confederation Nova Scotia. The legislature responded to fears of jury packing by creating more complex procedures for jury selection. These jury selection systems relied for their implementation on committees composed of magistrates and sheriffs, officials who proved unreliable instruments for carrying out a more bureaucratic state policy. Juries also reflected, and influenced, debates about political parties, libel, and the public sphere. In the 1840s, Irish immigrants to Nova Scotia drew upon their experience of packed juries in Ireland to complain that they were systematically excluded from jury service. Political reformers also asserted that officials packed juries against them with their political opponents, especially in high profile libel cases in which tories attempted to silence the increasingly critical reform press. These libel cases highlighted the role of the jury in protecting freedom of the press and therefore reformers’ ability to challenge the tory leadership of the colony. The fierce complaints over jury selection irregularities led to the passage of reform legislation, though a final solution to the politicization of juries remained elusive with the emergence and acceptance of political parties in Nova Scotia.